Impact of the Iraq Marshlands Restoration Program on Livestock Population and Production in the Southern Marshes of Iraq - Ayied, Asaad Y.; Reiss, Peter (Journal of Buffalo Science, 2019)
The USAID Iraq Marshlands Restoration Program (IMRP) promoted the application of two promising initiatives tested from 2004 to 2006: (1) the introduction of alfalfa and maize fodder to feed and improve the nutrition of buffalo and (2) the creation of a veterinary service to increase livestock production and health. The livestock sector in the marshlands has seen dramatic improvement since IMRP ended in 2006. These changes are across the board in the absolute number of livestock (from 66,700 heads in 2006 to 111,525 heads in 2017) and in their increasing diversity (buffalo were 74.33% of all livestock in 2006 but decreased to 70.33% in 2017). Buffalo, specifically, had greater birth weight (40 kg in 2006 and 45.6 kg in 2017), greater daily growth rates (0.3 kg in 2006 and 1-1.25 kg in 2017), higher daily milk yields (8.81 kg/day in 2006 and 9.69 kg/day in 2017), and longer lactation periods (150 days in 2006 and 238 days in 2017). There have been accompanying advances in the closely related meat and dairy markets. Live weight and market prices for buffalo and cattle have increased three- to four-fold. Rising daily milk yields also sparked the creation of cottage industries to produce dairy products using higher fat buffalo milk. These changes all point to an increasingly healthy and dynamic livestock sector in the marshlands. However, other anticipated changes in the marshlands did not meet expectations. In 2006, IMRP predicted a strong shift away from the historical dominance of buffalo ownership to a more diversified pattern of ownership that included the relatively newly introduced cattle and a rapid increase in sheep holdings, making the latter the dominate animal. Instead, buffaloes have continued to be the vastly most numerous animals owned in the marshlands. In 2017, they ranged from 65 to 75% of all livestock holdings. Greater access to reflooded marshes by buffalo herders and increased financial earnings realized from meat and dairy production may help to explain the continued reliance on buffalo ownership. IMRP’s introduction of a veterinary service dedicated to working in the marshlands villages was far less successful but highly regarded by Marsh Arabs, being the first time that the services were offered in the marshes.